2007
DOI: 10.1167/7.11.6
|View full text |Cite
|
Sign up to set email alerts
|

Collinear facilitation in color vision

Abstract: The detection of a luminance-defined Gabor is improved by two high contrast, aligned, flanking Gabors, an effect termed collinear facilitation. We investigate whether this facilitation also occurs for isoluminant chromatic stimuli, and whether it can occur for chromatic targets with luminance flanks and vice versa. We measured collinear facilitation for Gabor stimuli (0.75 cpd, 1 octave bandwidth) of three different contrast types: achromatic, red-green that isolates the L/M-cone opponent mechanism, and blue-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 62 publications
3
8
0
Order By: Relevance
“…The present results demonstrate that orientation tuning is not unique to the M/L-opponent pathway and are consistent with a study in V1 of another dichromat—the gray squirrel—that reported identical orientation selectivity in cone-opponent and non-opponent neurons (Heimel et al, 2005). Our results are also consistent with recent fMRI and psychophysical studies in humans that provide evidence for orientation-selective responses to S-cone-isolating stimuli in V1 (Beaudot and Mullen, 2005; Huang et al, 2007; Sumner et al, 2008; Wade, 2009). …”
Section: Discussionsupporting
confidence: 92%
“…The present results demonstrate that orientation tuning is not unique to the M/L-opponent pathway and are consistent with a study in V1 of another dichromat—the gray squirrel—that reported identical orientation selectivity in cone-opponent and non-opponent neurons (Heimel et al, 2005). Our results are also consistent with recent fMRI and psychophysical studies in humans that provide evidence for orientation-selective responses to S-cone-isolating stimuli in V1 (Beaudot and Mullen, 2005; Huang et al, 2007; Sumner et al, 2008; Wade, 2009). …”
Section: Discussionsupporting
confidence: 92%
“…This transformation means that these cells respond to cues for form, such as boundaries and edges, and may take signals from color or black and white as needed. Neurophysiological evidence that V1 neurons can be both color-selective and orientation-selective is consistent with recent functional magnetic resonance imaging and psychophysical studies in humans showing orientation-selective responses to color stimuli (Beaudot and Mullen, 2005; Engel, 2005; Beaudot and Mullen, 2006; Huang et al, 2007; Sumner et al, 2008). The differences from the originally proposed double-opponent cell necessitate a revision of the model (Figure 3E).…”
Section: Striate Cortex Mechanismssupporting
confidence: 87%
“…A similar argument against uncertainty reduction has been elaborated by Chen and Tyler (2008). Morgan and Dresp (1995), Williams and Hess (1998), Huang and Hess (2007), Huang, Mullen, and Hess (2007), Summers and Meese (2009), Meese and Baker (2009), and Wu and Chen (2010) also presented data that prompted them to rule out uncertainty reduction as the cause of flanker facilitation.…”
Section: Discussionsupporting
confidence: 52%